Aortic regurgitation after transcatheter aortic valve implantation: incidence and early outcome. Results from the German transcatheter aortic valve interventions registry. Issue 11 (12th March 2011) - Abdel-Wahab, Mohamed; Zahn, Ralf; Horack, Martin; Gerckens, Ulrich; Schuler, Gerhard; Sievert, Horst; Eggebrecht, Holger; Senges, Jochen; Richardt, Gert; ,
Abstract : Background: Significant aortic regurgitation (AR) is rare following surgical aortic valve replacement and has been associated with worse outcome. Following transcatheter aortic valve implantation (TAVI), AR is common, but little is known about its determinants and its effect on clinical outcome. Objective: To evaluate early outcome and risk factors possibly associated with AR after TAVI. Methods: Data were analysed from 690 patients with severe aortic stenosis treated with TAVI enrolled in the prospective multicentre German transcatheter aortic valve interventions registry. The occurrence of AR was evaluated angiographically after device deployment and removal of the catheter and guidewire. Significant AR was defined as AR≥2/4. Results: The study population's mean age was 81.4±6.3 years and men represented 44%. The mean logistic Euroscore was 20.4±13.1%. Overall, 84% of patients received the Medtronic CoreValve system and 16% received the Edwards Sapien valve. Significant AR occurred in 119 patients (17.2%). Factors independently associated with significant AR were aortic valve area (adjusted OR=0.10), annulus measurement by transoesophageal echocardiography (adjusted OR=1.94), male gender (adjusted OR=1.80), cardiogenic shock (adjusted OR=1.94) and renal failure (adjusted OR=0.53). In-hospital death rates were significantly higher in patients with significant AR than in those with no/mild AR (15.1% vs 6.7%, OR=2.50, 95% CI 1.37 to 4.55), as were rates of low cardiac output (20% vs 4.4%) and respiratory failure (16.5% vs 7.1%). Using multivariate analysis, the presence of post-procedural AR≥2/4 remained a strong independent predictor of in-hospital death (adjusted OR=2.43, 95% CI 1.22 to 4.85). Conclusion: Significant AR after TAVI is common and is associated with increased in-hospital mortality. Long-term follow-up is critical to further define the impact of residual AR on clinical outcome. Until these data become available, every effort should be made to prevent and treat this complication.